SAT0201 Relationship of Matrix Metalloproteinase-3 With Pulmonary and Joint Involvement in Scl-70 Positive Systemic Sclerosis Patients. (23rd January 2014) - Zlatanovic, M.; Sefik-Bukilica, M.; Ostojic, P.; Prodanovic, S.; Seric, S.; Radunovic, G.; Radak-Perovic, M.; Damjanov, N.
Abstract : Background: Extracellular matrix degradation is regulated mainly by matrixmetalloproteinases (MMPs). MMP-3 can degrade many components of the extracellular matrix and an increase in serum MMP-3 concentration has been proposed as a synovial derived marker of inflammation. Objectives: To determine matrix metalloproteinase-3 (MMP-3) serum levels in anti Scl 70 positive patients with systemic sclerosis (SSc) and to study clinical significance and the relationship between MMP-3 and pulmonary and joint involvement Methods: Forty-seven anti-Scl 70 antibodies positive patients with systemic sclerosis (43 female, 4 male) and 50 healthy controls were included in the study. All SSc patients underwent standard assessment, including laboratory tests, physical examination with joint assessment, chest X-ray and pulmonary functional tests, including diffusion capacity for carbon monoxide (DLco) and forced vital capacity (FVC). Levels of MMP-3 were measured with specific ELISA kit (Aeskulisa DF) with normal range between 18-60 ng/ml for female and 24-120ng/ml for male. Results: SSc patients had significantly higher MMP-3 concentration compared to healthy donors 122.64±188.40 vs. 57.4±46.79, p<0.001. Twenty-two (46.8%) SSs pts had increased MMP-3 levels above normal range and those had more frequently pulmonary fibrosis (p<0.001) and arthritis (p<0.001). Patients with increased levels of MMP-3 had significantly more frequently reduction in DLco <75% predicted (p<0.001). Conclusions: In 47 patient with systemic sclerosis and anti-Scl 70 positive antibodies, high levels of MMP-3 significantly positively correlate with pulmonary fibrosis, DLCo < 75% predicted and joint involvement (arthritis). Disclosure of Interest: None Declared